2022
DOI: 10.1186/s12905-022-01633-0
|View full text |Cite
|
Sign up to set email alerts
|

Women's experiences in the transition to menopause: a qualitative research

Abstract: Background Around the time of transition to menopausal period, women experience mental, and psychological disorders that require adequate attention to these symptoms. This study aimed to explore the experiences of women in the face of premenopausal symptoms. Methods This qualitative study was conducted using a content analysis method in Javanrood, Iran, in 2020. The data were collected through in-depth semi-structured face to face interviews with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…This study has contributed understanding into the importance of social connections among women with learning disabilities in menopause, particularly with those sharing similar experiences. Although this is already recognised within the neurotypical population (Refaei et al, 2022), in-depth consideration of the value of social connections in menopause is novel to literature pertaining to experiences of women with learning disabilities. For some, menopause represented improved ability and confidence to go out, engage in activity and socialise.…”
Section: Discussionmentioning
confidence: 99%
“…This study has contributed understanding into the importance of social connections among women with learning disabilities in menopause, particularly with those sharing similar experiences. Although this is already recognised within the neurotypical population (Refaei et al, 2022), in-depth consideration of the value of social connections in menopause is novel to literature pertaining to experiences of women with learning disabilities. For some, menopause represented improved ability and confidence to go out, engage in activity and socialise.…”
Section: Discussionmentioning
confidence: 99%
“…6 These experiences of menopause are influenced by many factors like beliefs, values prevalent in the socio-cultural settings, the background characteristics of women and the ways in which the women adapt to the changes in this phase of life. 7 Previous studies 7,8 revealed post-menopausal women experienced physical and emotional changes, changes in marital and family relationships, and adopted different coping strategies to enhance their physical and emotional wellbeing, to meet their felt needs and support from family.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are relatively few studies on the life experiences of menopausal women. Studies conducted in the Western Province of Sri Lanka [ 22 ], Iran [ 23 , 24 ], and Southeastern Louisiana [ 25 ] shed light on women’s understanding and experience of menopause and its impact on their lives. Some studies focused on the menopausal experience of women with diseases.…”
Section: Introductionmentioning
confidence: 99%